Paper as an Analytic Resource for the Design of New Technologies - Sellen, Abigail; Harper, Richard (Proceedings of CHI '97 ( Atlanta, GA.), 1997)
We report on an examination of work practice in a knowledge-based, document-intensive organisation and describe the role of paper in that work. We show how such an examination can provide a resource for (1 ) the determination of system design modifications that can be undertaken in the short term; (2) the determination of entirely new systems design requiring longer term research and development; and (3) helping to specify where paper will continue to be used in future document-related work practice.